ҲАШАРОТЛАРНИНГ ЎСИМЛИККА ТАЪСИР КУЧИНИ АНИҚЛАШ МЕЗОНЛАРИ (Scientific journal of the Fergana State University, 2023)
The article presents the results obtained in the study of the criteria for the influence of insects to plants. On the basis of the proposed criteria, it is possible to evaluate the influence of different insects on agrocenoses. The criteria are explained as a result of a change in the damaged plant. Also, these criteria provide an opportunity to draw conclusions about the role and importance of insects in evolutionary development.